Dampak Pengembangan Pariwisata Pendakian Puthuk Gragal Terhadap Keseahteraan Ekonomi Masyarakat - Putri, Oktavia Rizqiana; Rachmawati, Lucky (Universitas Negeri Surabaya, 2023)
The tourism sector has the potential to be the leading sector in order to increase regional income sources, with the aim of improving the welfare and prosperity of the people, encouraging regional development. By paying attention to the development of the tourism sector, it is able to encourage and be able to improve aspects of economic and social life, as well as norms that exist in society. This research uses a deductive approach, with data collection methods through interviews, observation, and documentation. The results of this study with the development of tourism Puthuk Gragal climbing further increase income, so that people are able to meet needs such as education costs and health costs, as well as the opening of employment opportunities.